Ten-eleven translocation 2 interacts with forkhead box O3 and regulates adult neurogenesis - Xuekun Li (Nature Portfolio, 2017)
Epigenetic modifications, such as DNA methylation, play an important role in adult neurogenesis. Here the authors show that Tet2, which converts 5mC to 5hmC, interacts with the transcription factor Foxo3a and regulates critical genes related to the proliferation and differentiation of adult neural stem cells.